Analisis Anggaran dan Pengelolaan Keuangan Pada Usaha Seblak Gian - Dhermawan, Faisal; Sari, Putri Delvina; Fauziah, Yupita Asmul; Dalilla, Dea; Priyandini, Marliana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Money related administration of medium-sized businesses is regularly confronted with the failure of medium-sized businesses to isolated their individual accounts from their commerce funds, which can cause challenges in calculating the level of benefits and misfortunes for medium-sized businesses. In reality, money related administration is one of the markers that must be taken under consideration to decide the victory or disappointment of a commerce. In expansion, destitute monetary administration implies that medium-sized businesses are incapable to require preventive activity to anticipate potential mishandle in their commerce (Amaliyah Hetika, 2023). This research was carried out because the Seblak Gian business is increasingly crowded with visitors, this culinary delights that have entered almost all regions in Indonesia have unique and varied flavors. The reason of composing this work is to assess the viability of Seblak Gian’s budget in overseeing its financial resources and give proposals for enhancements that ought to be made within the future. The research method used is a qualitative research method, by coming directly to the field, conducting interviews, collecting data, namely observation and documentation. The results of this research state that Seblak Gian still needs to continue to reform its business so that consumers are interested in enjoying Seblak Gian and continue to carry out regular financial evaluations.